Fracture reliability concern of (Au, Ni)Sn4 phase in 3D integrated circuit microbumps using Ni/Au surface finishing. (1st July 2016) - Liu, Yingxia; Chen, Yi-Ting; Gu, Sam; Kim, Dong-Wook; Tu, K.N.
Abstract: Au surface finishing on Ni layer in solder joints can lead to the replacement of β-Sn by (Au, Ni)Sn4 phase in microbumps. A thorough crack in (Au, Ni)Sn4 is found after the sample being annealed at 150 °C for 1000 h. Phase transformation of (Au, Ni)Sn4 to Ni3 Sn4 and AuNi2 Sn4 is observed. This transformation will lead to − 10.5% volume shrinkage and may result in tensile stress, which becomes the reason for a thorough crack formation. Kirkendall voids have been found at the interface between Ni3 Sn4 and electroplated Ni layer. Marker movement indicates that there was a dominant Ni diffusing flux. Graphical abstract: